De-Settlering Ourselves: Conference Reflections - Skott-Myhre, Kathleen; Kouri, Scott; Skott-Myhre, Hans (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This article explores the complexities of settler relations within the context of an academic conference hosted by Indigenous hosts and inclusive of Indigenous ceremony and content. The authors explore a range of questions related to their settler identities as participants in the conference. How are we as settlers to engage in a conference entitled “CYC in Action”, held at an institution constructed on Indigenous land, and dedicated to the promulgation of Western thought and culture? How are we to encounter the ghosts of those Indigenous peoples destroyed and removed from this very geography? How are we to be positioned in relation to our Indigenous colleagues who are reclaiming fragments of this colonized space through ceremony, buildings, and the introduction of sacred objects and totems? Should we adopt the studied neutrality of scholars, the moral high ground of activists, or the inclusive posture of the “good” settler? Do we find ways to be comfortable in the space? Is it an option to seek to be comfortable? Is our “Whiteness” as settlers our passport to enter Indigenous space and claim a right to be there as “friends”? Under the contested relation of a conference taking place on stolen lands that includes both the thieves and the survivors of the theft, who is the host and who determines the conditions of inclusion?